Management of Dakwah In Religious Activities at Mosque - Laila Khasanah, Nevi; Arikarani, Yesi; Ngimadudin; Hecksa Manora; Akip, Muhamad (Institute of Education and Social Research, 2024)
The problem in this research is poor management of religious activities. The aim of this research is to describe the description of da'wah management in religious activities in mosques. And describe what factors support and hinder the management of da'wah in religious activities in mosques. This research was operated using a qualitative approach with a descriptive research type. The researcher used purposive techniques in determining research subjects as well as observation, interviews and documentation as methods of gathering information related to this research. Use of source triangulation as a method of finding data validity. The results of this research provide a description that the management of da'wah in religious activities in mosques is managed through planning stages carried out using a deliberation system in planning a religious activity, grouping carried out by grouping types and themes of religious activities, as well as supervision that is determined and carried out by setting standards for religious activities. Meanwhile, the supporting and inhibiting factors for da'wah management in religious activities in mosques consist of internal factors and external factors, namely mosque management factors and also mosque congregation factors.